HEPATOZOON SPP. INFECT FREE-RANGING JAGUARS (PANTHERA ONCA) IN BRAZIL - Furtado, Mariana Malzoni; Metzger, Betina [UNESP]; Almeida Jacomo, Anah Tereza de; Labruna, Marcelo Bahia; Martins, Thiago Fernandes; O'Dwyer, Lucia Helena [UNESP]; Paduan, Karina dos Santos [UNESP]; Porfirio, Grasiela E. O.; Silveira, Leandro; Sollmann, Rahel; Taniwaki, Sueli Akemi; Torres, Natalia Mundim; et al. (Amer Soc Parasitologists, 2017)
This study investigated the presence of Hepatozoon spp. in jaguars (Panthera onca) and domestic animals in the Cerrado, Amazon, and Pantanal biomes of Brazil. Between February 2000 and January 2010, blood samples were collected from 30 jaguars, 129 domestic dogs (Canis lupus familiaris), and 22 domestic cats (Felis catus) for molecular tests. All of the jaguars from the Pantanal (n = 22) and Cerrado (n = 4) and 3 of 4 jaguars from the Amazon were positive for Hepatozoon spp. Domestic dogs (62.8%) and cats (31.8%) were also positive for the agent. Hepatozoon nucleotide sequences from jaguars and domestic cats grouped with other Hepatozoon felis, whereas Hepatozoon from domestic dogs showed high similarity to Hepatozoon canis. Different species of Amblyomma were identified as parasitizing the jaguars and may act as vectors for Hepatozoon spp. Jaguars from the 3 sites were healthy and did not seem to be threatened by the hemoparasite within its population or environments. Most likely, jaguars play an important role in the maintenance of Hepatozoon spp. in nature.